Research Progress and Prospects for Polymeric Nanovesicles in Anticancer Drug Delivery - Li, Dan; Zhang, Xi; Chen, Xiao; Li, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Nanocarriers are attracting increasing attention in drug delivery, especially in cancer therapy. Significant advances have been reported, including hydrophilic molecules with high loading capacity, controllable drug release, rapid and smart responses to stimuli and versatile functionalities. Among all nanocarriers, polymeric vesicles are the most promising candidates owing to their easy design and modalities. Polymeric nanovesicles can be prepared using a variety of methods and are suitable for encapsulating hydrophilic drugs, including weakly basic or acidic hydrophilic drugs, and various biological macromolecules. Polymeric nanovesicles have thick hydrophobic membranes with adjustable properties and can be used to treat or diagnose cancer via hydrophobic drugs or fluorescence probes through hydrophobic interactions. The biodegradability, elasticity, permeability, mechanical stability, vesicle membrane thickness, and drug release of polymeric nanovesicles can be regulated by modulating the type and molecular weight of the polymers comprising the vesicles. Therefore, research on polymeric nanovesicles is important for developing potential new cancer treatments.